2012
DOI: 10.1080/02640414.2012.718092
|View full text |Cite
|
Sign up to set email alerts
|

Can scapular and humeral head position predict shoulder pain in adolescent swimmers and non-swimmers?

Abstract: The aims of this study were to determine whether scapular and humeral head position can predict the development of shoulder pain in swimmers, whether those predictors were applicable to non-swimmers and the annual rate of shoulder pain in adolescent swimmers and non-swimmers. Forty-six adolescent swimmers and 43 adolescent non-swimmers were examined prospectively with a questionnaire and anthropometric measures. The questionnaire examined demographic and training variables. Anthropometric measures examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 74 publications
0
25
1
Order By: Relevance
“…Where a study used multiple classifications, this was dichotomised into with or without scapular dyskinesis for meta-analysis 24 36 37. Only one study differed substantially from these methods of visual classification, using measurement of distance between anatomical landmarks 35. The author of that study provided dichotomised data (with or without scapular dyskinesis) using receiver operating characteristic analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Where a study used multiple classifications, this was dichotomised into with or without scapular dyskinesis for meta-analysis 24 36 37. Only one study differed substantially from these methods of visual classification, using measurement of distance between anatomical landmarks 35. The author of that study provided dichotomised data (with or without scapular dyskinesis) using receiver operating characteristic analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The results of this sensitivity analysis demonstrated that the presence of scapular dyskinesis at baseline was indicative of a 54% increased risk of shoulder pain (RR=1.54, 95% CI 1.13 to 2.10, I 2 =40%). To determine the effects of a different assessment of scapular dyskinesis, McKenna et al 35 was excluded. The results of this sensitivity analysis demonstrated that the presence of scapular dyskinesis at baseline was indicative of a 28% increased risk of shoulder pain (RR=1.28, CI 0.93 to 1.76, I 2 =17%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective study by Mckenna et al 7 investigated whether humeral head position is predictive of the development of shoulder pain in competitive swimmers. They studied 46 adolescent swimmers.…”
Section: Shoulder Posturementioning
confidence: 99%
“…Rates vary, depending on age, level of competition, swim stroke, amount of training, time of season and the definition of shoulder pain. Symptoms may begin at an early age, with 21% of swimmers aged 8–11 reporting significant pain, but high school swimmers were found to be the most symptomatic age category 6 7. A belief even exists that shoulder pain is normal and should be tolerated to complete practice 8.…”
Section: Introductionmentioning
confidence: 99%